Study of arthroscopic superior capsule reconstruction in the treatment of irreparable rotator cuff tears - Sun, Kai; Li, Yijin (Frontiers in Surgery, 2023)
Background: The objective of this study was to investigate the clinical outcome and radiographic findings after arthroscopic superior capsule reconstruction (ASCR) for irreparable rotator cuff tears. Methods: From 2018 to 2020, 11 shoulders patients with irreparable rotator cuff tears underwent ASCR using fascia lata weaving mesh. Physical examination, radiography, clinical outcome scores and magnetic resonance imaging (MRI) were performed before surgery and average follow-up was 20 months (18 to 24 months) after surgery. Results: Average clinical outcome scores improved significantly at the final follow-up, 94.7 points by ASES (range, 85 to 100 points), 34.5 points by UCLA (33 to 35points)(P<0.05). Mean active elevation increased significantly from 30.1°to 150°(P<0.05) and external rotation increased from 30°to 59.2°(P<0.05). Acromiohumeral distance (AHD) increased from 3.9±0.6 mm preoperatively to 10.1±0.7mm postoperatively (P<0.05). No patients had graft tear or tendon retear during follow-up. Conclusions: ASCR can restore function of shoulder joint with irreparable rotator cuff tears. Our results suggest that this reconstruction technique obtained good clinical and radiographic outcome which can provide a reliable method in treatment of irreparable rotator cuff tears.